2000
DOI: 10.1034/j.1399-3003.2000.15e06.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma mortality in Danish children and young adults, 1973-1994: epidemiology and validity of death certificates

Abstract: Several reports indicate that asthma mortality has increased during the last few decades. International comparisons reveal some striking differences in the pattern of asthma mortality. The authors investigated the asthma mortality rate in the Danish child and youth population 1973–1994 and studied the validity of death certificates. The authors reviewed all death certificates coded as asthma death in the International Classification of Diseases (ICD 8–ICD 10 (1994)) and adjacent respiratory code numbers for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
1
24
0
2
Order By: Relevance
“…Instead, a substantial number of studies assess how well the data suit a particular purpose. Thus, some try to assess [9,11,13,23,24,34,37,43] how well reported causes of death mirror the prevalence of a particular condition at death, whether or not it caused the death. Other studies always assign the death to a specific condition if present, regardless of the other conditions from which the decedent may have suffered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a substantial number of studies assess how well the data suit a particular purpose. Thus, some try to assess [9,11,13,23,24,34,37,43] how well reported causes of death mirror the prevalence of a particular condition at death, whether or not it caused the death. Other studies always assign the death to a specific condition if present, regardless of the other conditions from which the decedent may have suffered.…”
Section: Discussionmentioning
confidence: 99%
“…In eight studies panel members first assigned a cause of death independently, and the panel then jointly assessed cases in which the members had assigned different causes of death. Five studies used other methods to adjudicate differences between panel members: majority decision [13,21], decision by the panel chair [22], decision by an independent specialist [23], or excluding such deaths from the analysis [24]. In four papers, the panel procedures were not described.…”
Section: Review Procedures (Table 2)mentioning
confidence: 97%
See 1 more Smart Citation
“…Respiratory diseases, except for pulmonary neoplasm [24], may have more ambiguous autopsy criteria than cardiovascular diseases or neoplasms in other organs. JøRGENSEN et al [25] stated that after autopsy and histological examination of asthma deaths in Denmark, many cases were coded by the pathologist as due to emphysema and/or bronchitis. However, E40 groups the chronic inflammatory lower respiratory diseases and may thus improve its validity.…”
Section: Discussionmentioning
confidence: 99%
“…234,270 In their review of the methods used in studies which assessed cause-of-death accuracy of deaths reported to official mortality statistics agencies, Johansson et al found that most studies, 89%, made use of medical records. Two of these studies assessed the accuracy of asthma deaths in Denmark, 244,271 both finding that the accuracy of death certification in asthma deaths was poor. In official statistics for Warsaw in Poland, May found that mortality from 120 asthma and COPD has been underestimated when compared to hospital and clinic records.…”
Section: Medical Record Reviewmentioning
confidence: 99%